Storytelling in Business Presentations: A Qualitative Study at PT Changshin Reksa Jayaan Organizational Communication Strategy in Businnes Presentations: A Qualitative Study at PT Changshin Reksa Jaya - Farhan Dimas Subagja (Ravine Publisher, 2026)
Storytelling is a strategic approach in organizational communication that not only conveys information but also builds meaning, emotion, and collective culture. However, the use of storytelling by corporate leaders in business presentations within the manufacturing sector remains underexplored, especially in local contexts such as Garut Regency. This study aims to examine how storytelling techniques are applied by leaders of PT Changshin Reksa Jaya to deliver strategic messages both internally and externally. This research employed a qualitative descriptive method through a literature study approach, drawing upon company documentation and local academic references. The findings reveal that storytelling is utilized in three key areas: safety and motivation training (HSE), performance evaluation, and external corporate communication. Narratives are used to embed workplace safety values, foster team solidarity, and build a positive public image. The practical implication suggests that storytelling strengthens organizational culture and promotes participatory relationships with stakeholders. Theoretically, these findings reinforce the relevance of symbolic communication and narrative approaches in the context of local business communication.